NILAI-NILAI PENDIDIKAN KARAKTER GURU DAN MURID DALAM PERSPEKTIF KISAH MUSA DAN KHIDIR DALAM SURAT AL-KAHFI AYAT 60-82 - Nasir, Jamal Abd. (STAIN PAMEKASAN, 2018)
Character based education values of teacher and students from the perspective of the history of Moses and the prophet of Khidir in the Al-Qurâan Al- Kahfi verse 60-82 can be concluded that it is better for someone who wants to study to deliver their intention politely, with a strong determination and patience.Â Â The students should always respect the teachers and say sorry in advance if they do something wrong. Teachers should try as good as possible to explain the material so that the students understand the purpose and the intention of the subject. The message of this history is that studying has nothing to do with age, whether they are old or young. A student needs to come to the core of knowledge although it takes time and a distance. When the teaching and learning process, a student is not allowed to cut the teacherâs speech, even they have to keep their attitude to get the teacherâs willingness.